2012
DOI: 10.1007/s12651-012-0111-0
|View full text |Cite
|
Sign up to set email alerts
|

Wirkungen der Mindestlohnregelungen in der Gebäudereinigung

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…In seven of these eight studies, the employment effects were estimated using difference‐in‐differences methods. All the control group estimates came to the conclusion that the industry‐level minimum wages, some of which were relatively high, had had no negative employment effects (Bosch and Weinkopf, ; Möller, ). On the basis of this new evidence and the dissemination of the more recent research on minimum wages from the United States and the UK by non‐mainstream researchers, the conservative labour minister and then the Chancellor herself declared themselves in favour of further minimum wages at industry level.…”
Section: The Debate On a Statutory Minimum Wage In The Trade Unions Amentioning
confidence: 99%
“…In seven of these eight studies, the employment effects were estimated using difference‐in‐differences methods. All the control group estimates came to the conclusion that the industry‐level minimum wages, some of which were relatively high, had had no negative employment effects (Bosch and Weinkopf, ; Möller, ). On the basis of this new evidence and the dissemination of the more recent research on minimum wages from the United States and the UK by non‐mainstream researchers, the conservative labour minister and then the Chancellor herself declared themselves in favour of further minimum wages at industry level.…”
Section: The Debate On a Statutory Minimum Wage In The Trade Unions Amentioning
confidence: 99%
“…The study included an assessment of eight sectors in which the AEntG was applied. The evaluations published in 2011 unanimously concluded that no systematic negative effects on employment levels could be found, which ended discussions about the termination of sectoral minimum wages due to negative employment effects (Bosch and Weinkopf, 2012). Official evaluations of the SMW came to similar conclusions, albeit with some caveats.…”
Section: Effects Of Minimum Wages On Wages and Employmentmentioning
confidence: 94%
“…Looking specifically at Denmark and Germany, part-time work – especially contracts of fewer than 15 weekly working hours – is widespread in both countries’ cleaning sectors, with as many as 42% holding such contracts in Denmark compared to 50% in Germany (Table 1). These numbers are considerably higher than just a few decades ago, although the volume of working hours has remained fairly stable, at least in Germany, indicating a marked shift in cleaning employment towards part-time and marginal part-time work (Bosch et al, 2012; Larsen et al, 2019; Riedel, 2012) (Table 1).…”
Section: Precarious Employment Within European Industrial Cleaningmentioning
confidence: 98%
“…Therefore, these workers may receive a wage below the sector minimum when calculated on an hourly basis for the time they have worked. A particular form of such performance-related pay systems is the so-called ‘object wages’ method ( Objekt-Löhne ) in Germany, under which the cleaning companies agree to pay a lump sum for a specified ‘object’ (Bosch et al, 2012). In Denmark, a similar performance pay system exists – the so-called work-pace 130 scheme (Arbejdstakt 130) – where workers are expected to clean at a pace that corresponds to walking 7.49 km per hour, according to Danish interviewees (DI et al, 2017).…”
Section: Precarious Employment Within European Industrial Cleaningmentioning
confidence: 99%
See 1 more Smart Citation